Fine‐scale structure among mesophotic populations of the great star coral Montastraea cavernosa revealed by SNP genotyping. Issue 12 (20th May 2020) - Drury, Crawford; Pérez Portela, Rocío; Serrano, Xaymara M.; Oleksiak, Marjorie; Baker, Andrew C.
Abstract: Mesophotic reefs (30‐150 m) have been proposed as potential refugia that facilitate the recovery of degraded shallow reefs following acute disturbances such as coral bleaching and disease. However, because of the technical difficulty of collecting samples, the connectivity of adjacent mesophotic reefs is relatively unknown compared with shallower counterparts. We used genotyping by sequencing to assess fine‐scale genetic structure of Montastraea cavernosa at two sites at Pulley Ridge, a mesophotic coral reef ecosystem in the Gulf of Mexico, and downstream sites along the Florida Reef Tract. We found differentiation between reefs at Pulley Ridge (~68 m) and corals at downstream upper mesophotic depths in the Dry Tortugas (28–36 m) and shallow reefs in the northern Florida Keys (Key Biscayne, ~5 m). The spatial endpoints of our study were distinct, with the Dry Tortugas as a genetic intermediate. Most striking were differences in population structure among northern and southern sites at Pulley Ridge that were separated by just 12km. Unique patterns of clonality and outlier loci allele frequency support these sites as different populations and suggest that the long‐distance horizontal connectivity typical of shallow‐water corals may not be typical for mesophotic systems in Florida and the Gulf of Mexico. We hypothesize that this may be due to the spawning of buoyant gametes, which commits propagules to the surface, resulting in greater dispersal and lower connectivity than typically found between nearby shallow sites. Differences in population structure over small spatial scales suggest that demographic constraints and/or environmental disturbances may be more variable in space and time on mesophotic reefs compared with their shallow‐water counterparts. Abstract : Mesophotic reefs (30‐150 m) have been proposed as potential refugia that facilitate the recovery of degraded shallow reefs following acute disturbances at shallower depths, such as coral bleaching and disease. We find extensive population structure among mesophotic Montastraea cavernosa, even between nearby sites. Differences in population structure over small spatial scales suggest that demographic constraints and/or environmental disturbances may be more variable in space and time on mesophotic reefs compared with shallow‐water counterparts.